Marketing Strategy in the Development of Agricultural Product Based on Artificial Intelligent - Pratama, Tomy Adi; Nugraha, Achmad Surya; Fitria, Fitria (Proceeding International Conference on Information Technology and Business, 2023)
The next generation of information technology, embodied by big data technology, is developing so quickly that agricultural product production and marketing information services will follow a trend toward intelligent marketing of agricultural products based on big data technology. The purpose of this research is to examine Marketing Strategy in the Development of Agricultural Product based on Artificial Intelligent. The method employed in this research is a literature review conducted utilizing an online search methodology for national and international scientific journal articles on multiple journal search engines such as Google Scholar, Science Direct, and the Elsevier journals. The results show that Smart agricultural product marketing based on big data technology, a new wave of rapidly evolving information technology will be the development trend for agricultural product production and marketing information services. These methods need to be further improved as a result. The development, marketing, and distribution activities of agricultural product operators have started to use artificial intelligence (AI).Â Keywords: Marketing Strategy, Agricultural Product, Artificial Intelligent